Development of synchronverter control for induction motor connection - Bahron, Zakria Ahmed S. (2014)
More and more attention has been paid to the energy crisis due to the increasing energy demand from industrial and commercial applications. The utilization of renewable energy considered as one of the most promising electrical energy sources, which has grown rapidly in the last three decades. In this day and age, many power converter techniques have been developed to integrate renewable energy with the electrical grid. In this work, there is a new technical control is known as synchronverter control which is using the synchronous generator mathematical equations as a reference. This synchronverter control is connected with DC-AC three phase inverter to work as controller of output power to feed the load. In this control strategy, the output current of the controllable inverter is controlled by a feedback load current according to the current reference. The synchronverter technology has been applied to control the inverter for the induction motor connection. An experimental setup based on DSP (Digital Signal Processing) and dc drive board have been designed to implement the open and closed loop experiments. All experiments have been implemented on a test rig based on Matlab 20013a/simulink software and Code Composer Studio V6.0 to demonstrate the excellent performance of the proposed control strategies with stability of the system, sinusoidal currents and good dynamics. Finally, an improve control strategy based on the synchronverter control technology has been tested for three phase inverter for renewable energy applications to make the whole system behave as a synchronous generator.